Family prayers for the use of the Cree Indians [electronic resource] - Mackay, J. A. (John Alexander), 1838-1923. (London : Society for Promoting Christian Knowledge, 1881)
Text in Cree. At head of title note in Cree script. Electronic reproduction. Mode of access: Internet. 44